Assessment of the Knowledge and Practice of Generic Nursing Students About Cardiopulmonary Resuscitation - Khan, Ibrahim; Karimulhaq, .; Perveen, Kousar; Kausar, Syeda Tasneem (Biological and Clinical Sciences Research Journal, 2025)
Cardiopulmonary resuscitation (CPR) is a fundamental skill required of nursing professionals to improve patient outcomes during cardiac emergencies. Despite global efforts to integrate CPR into nursing education, evidence suggests persistent knowledge and practice gaps among students, particularly in resource-constrained settings like Pakistan. Objective: To assess the knowledge and practice levels regarding CPR among undergraduate nursing students at Superior University, Lahore. Methods: A descriptive cross-sectional study was conducted among 177 Bachelor of Science in Nursing (BSN) students across all four academic years. A structured, pre-validated questionnaire comprising 13 knowledge and nine practice items was administered. Data were collected using simple random sampling and analyzed using SPSS version 23. Descriptive statistics, including frequencies and percentages, were used to summarize the findings. Results: Out of 177 students, 55.4% were female and 50.8% were aged between 21 and 23 years. The majority were second-year students (37.3%). While 80.2% correctly identified the meaning of "BLS", only 47.5% knew how to respond to an unconscious, non-breathing individual. Knowledge about compression locations and AED use was low (30.5% and 31.6%, respectively). In terms of practice, 54.8% identified the adult CPR algorithm correctly, 64.4% knew the correct pulse check site, and only 45.8% identified proper AED pad placement. Awareness of ERC 2015 guidelines stood at 56.5%. Conclusion: The study identified critical gaps in both theoretical knowledge and practical competence of CPR among nursing students. Findings underscore the urgent need for curriculum enhancements, including simulation-based learning, regular refresher training, and inclusion of updated CPR protocols to strengthen emergency response readiness in Pakistani nursing education.